Lung point-of-care (POCUS) ultrasound in a pediatric COVID-19 case (2020)
The World Health Organization categorized coronavirus disease 2019 (COVID-19) as a pandemic due to its high contagion rate and widespread infectivity in February 2020. In the United States, one of the public health concerns is the adequacy of resources to treat infected cases. We describe a case of a previously well, 9-year-old obese boy who presented to the emergency department with shortness of breath, fever, abdominal pain, and cough with chest pain. He was diagnosed with COVID-19 through significant family contact, confirmed by polymerase chain reaction and found to be at high risk of venous thromboembolism due to abnormal d-dimer. Lung point-of-care ultrasound (POCUS) in the emergency department observed significant lung pathology, including pleural thickening, consolidation, and B lines. A chest X-ray found bilateral ground glass opacities and interstitial prominences consistent with viral pneumonia. Our case suggests that lung POCUS can provide adequate and rapid imaging to assess lung pathology of COVID-19 in a pediatric patient. As there is limited literature on use of lung POCUS in pediatric patients infected with SARS-CoV-2, our case emphasizes its function as a potentially efficient modality in bedside assessment.